City branding : exploring city brand of Kuala Lumpur / Vaani Manickam - Manickam, Vaani (2002)
The classical definition for branding is all about differentiating the product from its competitors for identification purposes. However, in recent years, brand being a sophisticated tool for countries, cities and destination. They are encouraged to think themselves as a brand. The competition between cities becomes aggressive in establishing its own image in order to attract stakeholders such as tourists, investors, business, student and skilled people. Kuala Lumpur, the capital city of Malaysia which is yet to mesh up the attributes and elements into a single brand. This research elicits information on attributes and elements to build a strong city brand through qualitative research strategy. The city‟s unique characteristics are identified through six objectives and its effectiveness is measured based on Anholt‟s (2006a) city branding model. 32 respondents from various groups of stakeholders who are believed to be the appropriate group of people who are involved in creation of the city‟s image have been interviewed for the purpose of this study. The collected data were content analyzed by using NVIVO software. The result shows that Kuala Lumpur has been perceived and branded as a modern and fast pace city which diversify in terms of cultural, food, art and lifestyle. The Petronas Twin Tower (KLCC) stands out firmly as the main icon of Kuala Lumpur together with other places of interest and shopping has been identified as main attraction for the city. The research further presents the implication of the study for place marketer and authority. Based on the element, attributes and the favorable image of the city identified in this study, the authorities will be able to better understand the orientation of Kuala Lumpur branding. Besides, they also can use identified attributes to promote the city as some characteristics can be used as selling point of the city.